DIGITAL MARKETING ADAPTATION AMONG ISLAMIC BUSINESSES IN EMERGING MARKETS: RESILIENCE STRATEGIES AGAINST GLOBAL PROTECTIONIST ECONOMIC TRENDS - Avid Leonardo Sari; Rahayu Kusumadewi; Dudang Gojali; Iwan Setiawan; Muhammad Zaky (Gunung Djati Conference Series, 2025)
This study explores how Islamic businesses in emerging markets are adapting their digital marketing strategies in response to rising global protectionist economic trends. Through an integrative literature review, the paper synthesizes scholarly findings from peer-reviewed journals and reputable sources published within the last decade. The research highlights that protectionist policies have intensified market entry barriers, disrupted supply chains, and challenged consumer accessparticularly in Muslim-majority developing economies. Islamic enterprises, driven by ethical principles and religious values, have increasingly leveraged digital tools to maintain competitiveness and resilience. The findings reveal that digital marketing adaptation is not merely a tactical response, but a strategic transformation rooted in cultural identity and contextual innovation. Moreover, the literature underscores the importance of social media, mobile commerce, and content personalization in shaping consumer engagement in these markets. Despite growing scholarly interest, existing studies often overlook the intersection between Islamic business values and technological adaptation. This review identifies a significant research gap in understanding how Islamic ethical frameworks influence digital marketing behavior. The paper contributes by offering a conceptual foundation for future empirical inquiry on resilient business practices within faith-based economies. Ultimately, the study advances theoretical and practical discussions on the digital transformation of Islamic businesses amid economic uncertainty.